EUROPEANISM VS EUROSCEPTICISM IN THE COUNTRIES OF CENTRAL AND EASTERN EUROPE - Georgy T. Georgiev (Контуры глобальных трансформаций: политика, экономика, право, 2017)
Euroscepticism is a comparatively new political phenomenon. It consists of many aspects, such as critics of Europeism as a political ideology of the EU. This ideology is syncretical and includes different elements of famous political thoughts by Hobbes, Locke, French Enlightenment and German classic philosophy. The core principles of europeism are principles of progressism, universalism (which is known as ground for the ideas of liberal democracy). Today europeism has replaced traditional ideologies of conservatism and socialism and created new types of quasi-religions. The main principles of this ideology are formed and implemented on the level of supranational European institutions. On contrary, euroscepticism restores principles of traditional ideologies, being a significant oppositional actor in relation to europeism. During the last years, euroscepticism has been taking strong positions on both national and supranational levels. Especially, this can be seen referring to the experience of Central Eastern Europe, which, nontheless, has a successful story of European integration. The case of Central Eastern European countries shows a nationalistic character of euroscepticism (in its economic and political senses) and illustrates the people’s reaction on practices of the transfer of values and political practices. In Bulgaria euroscepticism remains weak – its membership is still seen as the only alternative, keeping in mind the destroying effect of the country’s shift toward democracy and market. Bulgarian euroscepticism connects with the people’s hopelessness in relation the EU as an actor, which is to deal with national problems.